Treatment and clinical outcome in patients with femoral head fractures: a long-term follow-up - Regenbogen, Stephan; Watrinet, Julius; Beck, Markus; Osten, Philipp; Stuby, Fabian; Grützner, Paul Alfred; Jaecker, Vera (Archives of orthopaedic and trauma surgery, 2024)
A femoral head fracture (Pipkin fracture) is a rare but severe injury. The optimal treatment is controversial, and there is a lack of research focusing on treatment strategies. The study aimed to analyze the treatment strategies in comparison to the outcome in patients after traumatic hip joint dislocation (THD) with concomitant femoral head fractures.
Gesehen am 24.02.2025